Anatomic variations of the spleen: current state of terminology, classification, and embryological background - Varga, Ivan; Babala, Jozef; Kachlik, David (Surgical and radiologic anatomy, 2018)
A thorough understanding of the anatomy, physiology, and development of the spleen is essential for determining the pathophysiological mechanisms underpinning splenic diseases and congenital variations. The aim of this review is to briefly summarize current knowledge regarding the normal development of the spleen, and to provide an overview of clinically relevant congenital splenic variations. These include such variations as asplenia, polysplenia, hyposplenia, lobulation of spleen, accessory spleens, accessory splenic nodules, wandering spleen, splenogonadal and splenopancreatic fusion, splenic cysts, and cavernous haemangioma of the spleen. All of these congenital variations are also mentioned in internationally accepted embryological nomenclature, known as the Terminologia Embryologica. Interestingly, most patients who have these diseases are asymptomatic, and are often diagnosed only after an injury or during unrelated medical procedures. Using examples from published case reports, we highlight how an understanding of the embryology of the spleen and the etiology of its disease states would improve clinical practice.
Keywords: abnormality lymfatického systému; terminologie jako téma; Spleen; Terminology as Topic; anatomická variace; lidé; Anatomic Variation; slezina; Lymphatic Abnormalities; Humans